Early ultrastructural lesions of anti‐neutrophil cytoplasmic antibody‐ versus complement‐associated vasculitis. Issue 5 (15th June 2022) - Koike, Haruki; Furukawa, Soma; Mouri, Naohiro; Fukami, Yuki; Iijima, Masahiro; Katsuno, Masahisa
Abstract : This study aims to describe electron microscopic findings of vasculitis associated with anti‐neutrophil cytoplasmic antibody (ANCA) and complement. Sural nerve biopsy specimens were obtained from 10 patients with microscopic polyangiitis (MPA), a representative ANCA‐associated vasculitis, and six patients with nonsystemic vasculitic neuropathy (NSVN), who were negative for ANCA but positive for complement deposition. In patients with MPA, attachment of neutrophils to epineurial vascular endothelial cells, migration of neutrophils to the extravascular space via the penetration of the endothelial layer, and release of neutrophil components to the extracellular space were observed. Such neutrophil‐associated lesions were not observed in patients with NSVN. Nonetheless, morphological changes in epineurial vascular endothelial cells, such as increases in cytoplasmic organelles and cytoplasmic protrusions into the vascular lumen, were observed in patients with NSVN. Since these findings were observed where light microscopy‐based findings suggestive of vasculitis (e.g., the disruption of vascular structures and fibrinoid necrosis) were absent, they were considered early lesions that preceded the formation of the so‐called necrotizing vasculitis. In conclusion, this study enabled the visualization of distinctive early ultrastructural lesions associated with ANCA and complement. Further studies are needed to elucidate the molecular basis of the induction of these fine structural changes, which will contribute to the development of targeted therapies based on specific mechanisms of vasculitis.